Visual sound : classical concert experience design for millennials : thesis presented in partial fulfillment of the requirements for the degree of Master of Design at Massey University, Wellington, New Zealand - Sun, Shuying (Massey University, 2017)
This thesis explores ways of engaging millennials in meaningful and relevant experiences which they would not normally engage with. It uses classical music as its case study since the popularity of classical music with millennials is low and declining. This project carried out exploratory work in experience design, focused on identifying the factors that discourage young people from attending classical music concerts. It then proceeded to design a concert experience which would fulfill millennials’ social needs and expectations of what they hope to experience when attending a classical concert. Visual Sound is a prototype which supports the active engagement of audiences, enabling them to both participate and contribute in a multisensory orchestra experience through a mobile interface. Audience participation and music visualisation were combined to create a designed experience. Through research, development and testing, the thesis demonstrates principles that can be applied to engage millennial audiences.
Keywords: Concerts; Design; Psychological aspects; Generation Y; Attitudes; Experience design; Audience engagement; Interaction design; Active participation; Passive participation; Music-visualization; Co-creation; Social and communication needs; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Music; Classical music